Education Framework 2030: Do Vocational School Students Have Green Skills? - Fadhilah Mahanani Saputri; Suryo Ediyono (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to analyze the condition of the green skills of vocational students with three focus problems, namely the condition of the green skills of vocational students and their implementation in the curriculum, indicators of green student skills, and learning strategies used to improve skills of vocational students. green skills. The approach used in this research is qualitative. Data was collected through Google Scholars, ResearchGate, ScienceDirect, Sinta, and Scopus. Data were collected from 27 articles which were then analyzed using thematic analysis techniques. The results showed that the green skills of vocational students had not met the challenges of the job market because the dimensions of green skills had not been fully implemented in the curriculum. Green skills can be measured by indicators of the value of technical skills, knowledge, and attitudes required by workers in a green economy. Learning strategies to improve green skills use a project-based and problem-based approach that encourages critical, innovative and responsible thinking. The results of this study are expected to have implications for the vocational education process which is more oriented towards green competence in accordance with the demands of DUDIKA. Thus, the quality of SMK graduates increases and unemployment decreases.